2007
DOI: 10.1093/aje/kwm252
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Inflammatory Factors Associated with Positive Affect in Healthy Men and Women: The Whitehall II Study

Abstract: Positive affective states are associated with favorable health outcomes, but the underlying mechanisms are poorly understood. The authors assessed associations between positive affect, cortisol sampled over the day, and inflammatory markers (C-reactive protein and interleukin-6) among 2,873 healthy members of the Whitehall II study. Data for this study were collected in 2002-2004 in London, United Kingdom. Saliva free cortisol was assessed on waking, 30 minutes later, and four times over the day and evening. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
178
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(198 citation statements)
references
References 52 publications
16
178
3
1
Order By: Relevance
“…Psychobiological pathways linking positive emotions and health outcomes are not yet well understood but may include variations in the activation and/or control of neuroendocrine, autonomic, immune and inflammatory pathways. Positive emotional dispositions have been associated with enhanced parasympathetic nervous system control in CHD patients (Bhattacharyya et al, 2008), increased antibody response to a vaccine (Marsland et al, 2006), and reduced daily cortisol output (Polk et al, 2005;Steptoe et al, 2008). Positive dispositions could influence cognitive appraisal of potentially 'stressful' daily events, leading to lower threat perceptions and reduced activation of the autonomic nervous system and hypothalamic-pituitary (HPA) axis (Lazarus and Folkman, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychobiological pathways linking positive emotions and health outcomes are not yet well understood but may include variations in the activation and/or control of neuroendocrine, autonomic, immune and inflammatory pathways. Positive emotional dispositions have been associated with enhanced parasympathetic nervous system control in CHD patients (Bhattacharyya et al, 2008), increased antibody response to a vaccine (Marsland et al, 2006), and reduced daily cortisol output (Polk et al, 2005;Steptoe et al, 2008). Positive dispositions could influence cognitive appraisal of potentially 'stressful' daily events, leading to lower threat perceptions and reduced activation of the autonomic nervous system and hypothalamic-pituitary (HPA) axis (Lazarus and Folkman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from naturalistic studies indicates that positive affect over several days is inversely related to daily cortisol output, independent of negative affect (Polk et al, 2005;Steptoe et al, 2005Steptoe et al, , 2008. However, findings are not entirely consistent; in a study measuring cortisol and current mood amongst 556 women over five days, Jacobs et al (2007) found that only negative affect was independently associated with cortisol.…”
Section: Introductionmentioning
confidence: 99%
“…These data contribute to evidence that, unlike for post awakening AUCg, there may be no reliable association between the CAR and TWB in healthy populations (e.g. Garcia-Banda et al, 2014;Steptoe et al, 2008) . Indeed in their meta-analysis of PACS and psychosocial factors Chida and Steptoe noted that the relationship between the dynamic of the CAR (unlike for the AUCg) and general life stress was not statistically significant when only studies with high methodological quality were included in the analysis (Chida & Steptoe, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…For instance, opposite or null relationships have often been reported (e.g. Evans et al, 2007;Juster et al, 2011;Lovell et al, 2011;Stalder et al, 2010b;Steptoe et al, 2007;Steptoe et al, 2008;Thorn et al, 2006;Wahbeh et al, 2008;Wuest et al, 2000a). It is now recognized as essential to distinguish the CAR and AUCg measures of PACS.…”
Section: Introductionmentioning
confidence: 99%
“…Steptoe et al 2008;Tuck et al 2016). But because low-grade systemic inflammation is related to numerous other exposures and phenotypes, the assessment of its causal role in well-being is hampered by potential confounding.…”
Section: Biomarkers Toward Understanding the Happiness Exposomementioning
confidence: 99%